The Influence of Parenting on Adolescent Girls’ Cross-generational Sex Motivation and Potential Risks: The Case of Kinondoni District, Tanzania - Rugaimukamu, Neema; Msoka, Colman (Tanzania Journal for Population studies and Development, 2025)
This study examines the influence of parenting on the relationship between emotional cross-generational sex motivation and potential risks among adolescent girls in Tanzanian secondary schools. It explores how parenting styles and practices impact emotional cross-generational sex motivation, and help manage the associated risks. A mixed-methods approach was used, combining in-depth interviews and focus group discussions. A sample of 385 adolescent girls was selected through cluster random sampling. Quantitative data was collected via interviewer- administered questionnaires, and analysed using SPSS, while qualitative data was processed with NVivo 12. The findings revealed that parenting practices play a significant role in moderating emotional cross-generational sex motivation and reducing the associated risks. Parental involvement is essential in preventing risky sexual behaviours. Thus, it is recommended that community-based parenting education programmes be implemented to train parents in authoritative strategies; emphasizing communication, risk awareness, and supportive monitoring. Integrating cross-generational sex (CGS) risk education into the school curricula, fostering strong parent-teacher partnerships, and engaging local leaders and NGOs to challenge socio-cultural norms that normalize age-disparate relationships: all these are essential in addressing the problem. Likewise policy efforts should prioritize parental support within adolescent health and education frameworks so as to leverage Tanzania’s existing child protection systems.